Training Program for Injection Motorcycle Service in Improving Trainees' Hardskills at the Jember Job Training Center - Syachriar, Agiel; Purnamawati, Frimha; Sintiawati, Nani; Kuriawan, Didik (Universitas Negeri Padang, 2025)
The training program is an activity that serves to enhance the hard skills of participants, including those who are physically fit and those with disabilities. The improvement in hard skills among training participants is intended as preparation for entering the workforce. The hard skill enhancement provided to participants with disabilities in this training program focuses on servicing fuel-injected motorcycles, including managing tools, replacing drive chains, assembling and disassembling body covers, and maintaining electrical instruments (signals and lighting). Many participants with disabilities aspire to open their own workshops after participating in this fuel-injected motorcycle servicing training. This has led the researcher to investigate further the relationship between the fuel-injected motorcycle servicing training program and the improvement of hard skills among participants in the automotive department at the Jember Vocational Training Center, specifically in the two-wheeled automotive field. This study is correlational research with a quantitative approach, using a purposive area selection at the Jember Vocational Training Center. Data collection methods included questionnaires and documentation, with a total population sampling technique resulting in 15 respondents. Data were analyzed using rank-order correlation techniques. The results of this study, calculated using SPSS v25, show that the calculated correlation coefficient is greater than the table value, indicating a strong relationship between the fuel-injected motorcycle servicing training program and the improvement of hard skills in the two-wheeled automotive field. The conclusion of this study is that the alternative hypothesis is accepted, and the null hypothesis is rejected, as the correlation test between the two variables indicates a relationship. The researcher suggests that future studies should further explore relationships beyond the two-wheeled automotive field to enhance the connections that can be gained in two-wheeled automotive training.Keywords: Training program, hard skill improvement, people with disabilities.